Role of Platelet Inhibition in Microvascular Surgery - Cho, Eugenia H.; Ligh, Cassandra; Hodulik, Kimberly L.; Hollenbeck, Scott T. (Journal of Reconstructive Microsurgery, 2014)
Thrombosis remains a significant complication of microvascular free tissue transfer. Recent discoveries in the field of vascular biology have led to a greater understanding of thrombogenesis and the pivotal role that platelets play in the formation of a clot. However, current antithrombotic strategies in the clinical practice of free tissue transfer have not typically focused on platelet inhibition. Decades of cardiovascular clinical trials have delineated the essential role of platelet inhibitor therapy in patients with acute coronary syndromes and those undergoing percutaneous coronary interventions. Understanding the current treatment guidelines for antiplatelet therapy across the spectrum of patients with coronary heart disease may provide insights into their use in the prevention and treatment of thrombosis in microvascular surgery. In this review, we examine the current antiplatelet agents in clinical use and discuss the potential role of platelet inhibition in free flap surgery, particularly in the setting of repeated microvascular thrombosis.
Keywords: platelet inhibition; flap surgery; thrombosis; microvascular